A conditional model for estimating the increase in suicides associated with the 2008–2010 economic recession in England. Issue 9 (22nd June 2013) - Saurina, Carme; Bragulat, Basili; Saez, Marc; López-Casasnovas, Guillem
Abstract : Background: Although evidence of the effects of the economic crisis on suicides is quite low, a recent article shows that the increase in suicides in England between 2008 and 2010 could be associated with the rise in unemployment. Our study analysed whether this effect was the same for all regions of England, using a conditional model which explicitly allows estimation of regional time trends and the effects of unemployment on suicides at the regional level. Methods: Hierarchical mixed models were used to assess both, suicides attributable to the financial crisis and the association between unemployment and suicides. The number and the (age-standardised) rate of suicides, for men and women separately, were the dependent variables. We considered the nine English regions based on the NUTS 2 level. Results: There was an (not statistically significant) increase in the number of suicides between 2008 and 2010. The variation in rates was not statistically significant in England as a whole but there were statistically significant increases and decreases in some regions. Statistically significant associations between unemployment and suicides were only found at regional level. For men, statistically significant unemployment rates were positively associated with age-standardised suicide rates in the South West (0.384), North West (0.260) and North East (0.136), and negatively associated in the East of England (−0.444), East Midlands (−0.236) and London (−0.168). Conclusions: The study provides evidence that, even with statistically significant associations, finding variability, but no clear pattern, between trends and associations and/or numbers and rates might in fact suggest relatively spurious relationships; this is a result of not controlling for confounders.